Post-COVID-19 Implementation of Chemistry using the TPACK Approach: A Systematic Literature Review - Ahmad Fauzi Syahputra Yani; Ismi Zatya; Nurhafidhah; Mauliza; Hasby (Postgraduate, University of Mataram, 2026)
This systematic literature review examines the implementation of Technological Pedagogical Content Knowledge (TPACK) in chemistry education in the post-pandemic learning context, with particular relevance to the advancement of Sustainable Development Goal 4 (SDG 4) on quality education. The study aims to identify how TPACK has been implemented in chemistry learning and to analyze its effectiveness and efficiency. The review followed PRISMA guidelines and analyzed eight empirical articles published between 2022 and 2024 from Garuda, ERIC, Taylor & Francis Online, and ScienceDirect. The findings show that TPACK implementation in chemistry education mainly involves the integration of technological, pedagogical, and content knowledge through digital tools such as simulations, web-based learning, flipped learning, and virtual platforms. Most studies focused on pre-service and in-service chemistry teachers, emphasizing the development of TPACK competencies and technology-supported instructional practices. The review indicates that TPACK contributes to more interactive, flexible, and meaningful chemistry learning, particularly in explaining abstract chemical concepts and improving student engagement and learning performance. In conclusion, TPACK plays an important role in supporting quality chemistry education and may contribute to the advancement of SDG 4, provided that its implementation is supported by adequate infrastructure, continuous professional development, and institutional commitment.